2006
DOI: 10.2214/ajr.05.1058
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Stress Reaction of the Distal Humerus in Elite Tennis Players

Abstract: Stress injury to the distal humerus is a cause of chronic arm pain among elite tennis players and may be exacerbated during full competition. The degree of marrow edema on STIR MRI may be predictive of time to return to competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…[1][2][3] There is a large amount of literature on a similar marrow signal intensity pattern in joints outside the spine where symptoms and abnormal marrow signal intensity in long bones correlate with clinical symptoms and trauma or response to stress. [10][11][12][13][14] Likewise, the association of type 1 pedicle marrow signal intensity changes with pars and pedicle fractures and degenerative facet changes suggests they are related to biomechanical stress created by abnormal spinal segment motion. This or a similar mechanism may be at play in the vertebral bodies A, Right parasagittal T1-, T2-, and STIR-weighted images that demonstrate a discrete fracture line through the pedicles of L4 bilaterally without pedicle marrow signal intensity changes (long arrow) and a less obvious fracture line on T1 images through the L5 pedicle with concomitant type 1 pedicle marrow changes (short arrows).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] There is a large amount of literature on a similar marrow signal intensity pattern in joints outside the spine where symptoms and abnormal marrow signal intensity in long bones correlate with clinical symptoms and trauma or response to stress. [10][11][12][13][14] Likewise, the association of type 1 pedicle marrow signal intensity changes with pars and pedicle fractures and degenerative facet changes suggests they are related to biomechanical stress created by abnormal spinal segment motion. This or a similar mechanism may be at play in the vertebral bodies A, Right parasagittal T1-, T2-, and STIR-weighted images that demonstrate a discrete fracture line through the pedicles of L4 bilaterally without pedicle marrow signal intensity changes (long arrow) and a less obvious fracture line on T1 images through the L5 pedicle with concomitant type 1 pedicle marrow changes (short arrows).…”
Section: Discussionmentioning
confidence: 99%
“…2 As a result, mag- Stress Reaction of the Humerus in a High School Baseball Player netic resonance imaging was obtained, which showed a hyperintense bone marrow signal in the distal humerus on fluidsensitive sequences (FIGURE 2), which was consistent with a stress reaction of the distal humerus.…”
mentioning
confidence: 90%
“…Recently published studies have reported chronic injuries in this region 14. As a consequence of these injuries, the athlete is required to spend weeks or even months recovering and is unable to participate in on-court activities.…”
mentioning
confidence: 99%
“…Furthermore, most of the studies examining tennis-related bone stress injuries concentrate on injuries to the trunk and lower limbs 5 6. In fact, only three articles were retrieved that reported stress reactions involving the humerus in tennis players 3 4 7…”
mentioning
confidence: 99%
See 1 more Smart Citation